2021
DOI: 10.1186/s12986-021-00602-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and physiological analysis of the effect of calcium supplements on reducing bone loss in ovariectomized rats by increasing estradiol levels

Abstract: Background Data from the 2010–2012 Chinese National Nutrition and Health Survey showed that the vast majority of postmenopausal women in China had dual deficiencies in calcium and estrogen. Objective This study aimed to clarify whether calcium supplementation alleviated bone loss caused by calcium restriction combined with estrogen deficiency in rats. Methods Forty-eight female rats aged 9 weeks were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
(56 reference statements)
2
9
0
1
Order By: Relevance
“…erefore, PMO rat model was established by ovariectomy. E 2 is a female hormone that decreased in postmenopausal women [33,34], and BMD is a critical parameter of PMO [35]. ELISA showed that the serum E 2 and BMD levels decreased in PMO rats.…”
Section: Discussionmentioning
confidence: 97%
“…erefore, PMO rat model was established by ovariectomy. E 2 is a female hormone that decreased in postmenopausal women [33,34], and BMD is a critical parameter of PMO [35]. ELISA showed that the serum E 2 and BMD levels decreased in PMO rats.…”
Section: Discussionmentioning
confidence: 97%
“…It is estimated to be higher (more than 10%) in postmenopausal women [ 69 , 70 ]. Low vitamin D levels as well as together with insufficient calcium intake, estrogen deficiency in postmenopausal women and smoking contribute to osteoporosis [ 39 , 71 ]. The prevalence of osteoporosis and the expenditures associated with its treatment impose a significant socioeconomic burden [ 72 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…The main differences in glycerophospholipids metabolism were identified in phosphatidylethanolamines, phosphatidylcholines and ceramides. Additionally, it was found that E2 may affect changes in glycerophospholipids and glycerophospholipid metabolism was considered to be the main potential target pathway of E2 [ 71 ]. Zhao used UPLC-Q-TOF-MS-based lipidomics in combination with metabolomics and provided more detailed information about the lipidomic profiles of and alterations in fatty acids, glycerolipids, glycerophospholipids, sphingolipids and sterols in an ovariectomized mouse model of osteoporosis [ 73 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…A series of studies found that vitamin D levels can significantly alter amino acids, energy metabolism, levels of sugars and their derivatives, and organic acids in patients with OP, thus affecting the metabolomic outcome of OP ( 77 , 78 ). In addition, different blood calcium levels affected the metabolism of lipids and amino acids such as taurine, glycerophospholipids and glycine, thus causing changes in the metabolomic outcome of OP, which ultimately affected BMD and bone degeneration ( 79 , 80 ). Recent studies have found that temperature increases the total amount of polyamines in the body, and that inhibition of polyamine biosynthesis in the body limited the protective effect on bone ( 81 ).…”
Section: Metabolomics In Op Pathogenesis Researchmentioning
confidence: 99%